Strategi Guru Sejarah Berbasis Konstruktivisme dalam Internalisasi JSN 45 untuk Mendukung Visi Indonesia Emas 2045 - miskawi; Akhmad Arif Musadad (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This study examines the Strategy of History Teachers Based on Constructivism in the Internalization of JSN 45 to Support the Golden Indonesia Vision 2045. This study uses a descriptive qualitative method with a literature study approach, analyzing the theories of Dewey, Bandura, and Vygotsky as the basis for meaningful learning. Veterans are involved as models and sources of inspiration to provide real experiences (Dewey), to be role models of struggle values (Bandura), and to support the gradual learning process through scaffolding (Vygotsky). The internalization of values such as nationalism, unity, and sacrifice has been proven to help shape the character of the young generation who are resilient, moral, and actively contribute to nation building.